PENGARUH FAKTOR MODAL, BAHAN BAKU, TENAGA KERJA TERHADAP JUMLAH PRODUKSI PANCAKE DURIAN DI KOTA PEKANBARU - Dewi Sri Tia; Pailis Armas Eka; Aqualdo Nobel (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This research was conducted on the Durian Pancake industry in Pekanbaru City. The purpose of this study is to determine the effect of capital, raw materials, and labor on the production of Durian Pancake industry in Pekanbaru City. The data used are secondary and primary data. This secondary data was sourced from the Cooperative and UMKM offices of Pekanbaru City, while the primary data was obtained from as questionaire conducted through interviews with 9 respondents of the durian pancake industry in the City of Pekanbaru. The theory used in this study is a theory relating to production factors, namely the Cobb-Douglas production function. The Data analysis method in this research is descriptive quantitative research. The sampling technique in this study is a saturated sampling technique which is a sampling technique if all members of the population are used as samples, namely 9 samples of Durian Pancake industry in Pekanbaru City. Data processing using SPSS application version 23.0.the variables used are capital,raw materials, and labor in the Durian Pancake industry in Pekanbaru City. The result showed that the variables capital, raw materials, and labor had a significant effect on durian pancake production. The results of multiple linear regression, the coefficient of determination R2 value is 0.837.This means that capital, raw materials, and labor have an important role in the level of production in the durian pancake industry in the city of Pekanbaru.Keywords: Production, Capital, Raw Materials, Labor, and Durian Pancake